Crab Louse, Pthirus pubis (Linnaeus) (Insecta: Phthiraptera (Anoplura): Pediculidae) - H. V. Weems, Jr.; Thomas R. Fasulo (EDIS, 2002)
This document is EENY-103, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 1999. Reviewed May 2003.